The Effect of Micro and Nano Material on Critical Heat Flux (CHF) Enhancement - Sharef, Enas M.; Ali, Jamal M. A (Al-Khwarizmi Engineering Journal, 2019)
The Nano materials play a very important role in the heat transfer enhancement. An experimental investigation has been done to understand the behaviors of nano and micro materials on critical heat flux. Pool boiling experiments have used for several concentrations of nano and micro particles on a 0.4 mm diameter nickel chrome (Ni-Cr) wire heater which is heated electrically at atmospheric pressure. Zinc oxide(ZnO) and silica(SiO2) were used as a nano and micro fluids with concentrations (0.01,0.05,0.1,0.3,0.5,1 g/L), a marked enhancement in CHF have been shown in the results for nano and micro fluids for different concentrations compared to distilled water. The deposition of the nano particles on the heater surface was the reason behind the enhancement of the wettability of the surface which will increase the CHF, this nano particles deposition will form a porous layer and the mechanism of the formation of this layers is that as vapor bubbles grow, the evaporating liquid in the micro layer leaves behind Nano particles which then will be concentrated at the base of the bubble to form this pours layer. The higher wettability can produce CHF enhancement, the enhancement ratio of Nano fluid is observed to be higher than that of micro fluid, the optimum   enhancement ratios of nano fluid is (1 g/l) which observed to be 9.2 % for ZnO and 8.7% for Sio2, and also (1 g/l) for micro fluid which observed to be   8.1%for ZnO and 7.4%for SiO2.